Microsoft Sway Media for Students' Independent Learning in The Independent Curriculum Era - Dayu, Dian Permatasari Kusuma; Nafisah, Durrotun; Cindy, Agustin Hanivia (LPPM Universitas Terbuka, 2024)
In this article, the author tries to link literature studies related to the use of Microsoft Sway media for students' independent learning in the independent curriculum in elementary schools. Microsoft Sway media has various benefits, especially in elementary school learning. The Microsoft Sway application really helps teachers in the learning process in class. Microsoft Sway media really helps teachers in the learning process in class.From several studies such as relevant research plus supporting theories, it is stated that Media Sway is a media that has special features that can be used by a teacher to create digital-based interactive learning media.This media helps collect, format and share ideas, stories and teacher presentations on interactive screens that look attractive.The hope is that Microsoft Sway media can be used as a reference for every educator in creating an optimal learning atmosphere.